Библиометрический анализ документально-информационного потока по нанобиотехнологиям на основе реферативной базы данных «Scopus» (издательство «Elsevier») (Библиосфера, 2010)
On the basis of «Scopus» database (the abstract database produced by publisher «Elsevier») bibliometric analysis of document and information flow on nanobiotechnology is made. The structure of types and kinds of the publications, dynamics of publication activity for the period from 1990 to 2008, the list of the authors with the largest number of publications are revealed. The range of journals, in which the largest amount of documents, is determined, as well as the leading organizations and countries on the information production on the subject considered.